Guidelines for the diagnosis and treatment of osteoarthritis in China (2019 edition) - Zhang, Zhiyi; Huang, Cibo; Jiang, Quan; Zheng, Yi; Liu, Yi; Liu, Shengyun; Chen, Yingjuan; Mei, Yifang; Ding, Changhai; Chen, Min; Gu, Xin; Xing, Dan; et al. (Annals of Translational Medicine, 2020)
Osteoarthritis (OA) is a degenerative disease of middle-aged and elderly people, contributed a higher burden of disease in China and the world. In 2017, under the support of the Rheumatology and Immunology Expert Committee of the Cross-Strait Medical and Health Exchange Association. The objective was to develop an evidence-based diagnosis and treatment guideline for OA in China based on emerging new evidence. The guideline was registered at International Practice Guidelines Registry Platform (IPGRP-2018CN028). The grading of recommendations assessment, development and evaluation (GRADE) approach was used to rate the quality of evidence and the strength of recommendations, and the RIGHT (Reporting Items for Practice Guidelines in Healthcare) checklist was followed to report the guideline. The guideline provides recommendations for the OA diagnosis, disease risks monitoring and evaluate, treatment purpose and physical, medical and surgical interventions. This guideline is intended to serve as a tool for Chinese clinicians for the best decisions-making on diagnosis and treatment of OA.Osteoarthritis (OA) is a degenerative disease of middle-aged and elderly people, contributed a higher burden of disease in China and the world. In 2017, under the support of the Rheumatology and Immunology Expert Committee of the Cross-Strait Medical and Health Exchange Association. The objective was to develop an evidence-based diagnosis and treatment guideline for OA in China based on emerging new evidence. The guideline was registered at International Practice Guidelines Registry Platform (IPGRP-2018CN028). The grading of recommendations assessment, development and evaluation (GRADE) approach was used to rate the quality of evidence and the strength of recommendations, and the RIGHT (Reporting Items for Practice Guidelines in Healthcare) checklist was followed to report the guideline. The guideline provides recommendations for the OA diagnosis, disease risks monitoring and evaluate, treatment purpose and physical, medical and surgical interventions. This guideline is intended to serve as a tool for Chinese clinicians for the best decisions-making on diagnosis and treatment of OA.